Media Convergence as a Tool for the Formation and Use of Soft Power in Chinese Politics (International relations and international law Journal, 2022)
In the context of globalization and the rapid development of information and communication technologies, the ongoing struggle between states for power and influence on the system of international relations, in which the driving force is the desire of world political actors to ensure the successful implementation of their interests through diplomatic, military-strategic, economic, information -ideological and other means, the use of the integration of means of communication, the convergence and merging of various ways of transmitting information in the media space in order to achieve their political interests is of particular relevance. Media convergence in the political sphere and in international relations becomes for states claiming the status of a superpower an instrument of mass influence on the public, spreading their culture and influence, and enhancing the image of the country. However, it is the political aspect of this concept that is considered insufficiently broadly and deeply in academic science, which necessitates a more thorough study based on specific examples of its application in international and regional politics by the leading actors of the geopolitical arena. This article discusses the use of the concept of media convergence by China as an effective mechanism for using “soft power” in the global media space and in the media space of the Central Asian region. Positioning itself as a great power in a non-confrontational manner, the China, in order to strengthen its influence on the system of international relations, focuses on the media, its convergence and combination of various types and forms, active entry and functioning abroad, directing huge investments into this strategy. In conclusion, the author gives forecasts for the activation of the Celestial Empire policy to increase its positive image, including through the use of the concept of media convergence.Key words: media, soft power, China, Central Asia, media convergence.